Unveiling the Cyclical Patterns of Historical Wage Inequality among European Building Laborers - Akarsu, Mahmut Zeki (Ekonomika, 2023)
This scholarly investigation examines the historical wage disparities between skilled and unskilled building laborers, as well as gender-based disparities among unskilled male and female workers in major European metropolises including Vienna, Warsaw, Krakow, and Istanbul. While exploring inequality, the study reveals that significant events such as wars, pandemics, and economic fluctuations have a cyclical impact on wage and gender inequality throughout history. However, it should be noted that gender inequality was only examined in the UK. By delving into the dynamics of wage and gender inequality during the medieval and early modern eras of Europe, this study provides a deeper understanding of the complexities of these social issues.